Leaf nitrogen allocation to non-photosynthetic apparatus reduces mesophyll conductance under combined drought-salt stress in Ginkgo biloba - Li, Lehao; Zhou, Kai; Yang, Xin; Su, Xina; Ding, Peng; Zhu, Ying; Cao, Fuliang; Han, Jimei (Frontiers in Plant Science, 2025)
Leaf nitrogen allocation plays a crucial role in determining both photosynthetic function and structural development of plants. However, the effects of drought, salt stress, and their combination on leaf nitrogen allocation, and how these affect mesophyll conductance (gm) and photosynthesis, remain poorly understood. In this study, we first investigated variations in photosynthetic characteristics and leaf nitrogen allocation, and analyzed the relationship between gm and leaf nitrogen allocation ratios in Ginkgo biloba under drought, salt and combined drought-salt stress. The results showed that all stress treatments significantly reduced the photosynthesis in G. biloba, with the combined drought-salt stress having the most significant inhibitory effect on the plant’s physiological characteristics. Under combined drought-salt stress, the limitation of photosynthesis due to gm (MCL) was significantly greater than under individual drought or salt stress. In contrast, the limitation due to stomatal conductance (SL) was similar to that observed under drought but higher than under salt stress. No significant differences in biochemical limitations (BL) were found across all stress treatments. Further research suggests that the increase in MCL under combined drought-stress treatment may be linked to a greater allocation of leaf nitrogen to non-photosynthetic apparatus (e.g., cell structure) and a smaller allocation to photosynthetic enzymes (i.e., ribulose-1,5-bisphosphate carboxylase/oxygenase, Rubisco). This is supported by the positive correlation between gm and the proportion of nitrogen allocated to the carboxylation system (Pr), as well as the negative correlation with the non-photosynthetic nitrogen ratio (Pnp). These findings help to advance our understanding of the mechanisms of photosynthesis and plant adaptability under combined drought-salt stress.